Spins coupled to a Z2-Regge lattice in 4d - Bittner, Elmar; Janke, Wolfhard; Markum, Harald (Nuclear physics. Proceedings supplements, 2002)
We study an Ising spin system coupled to a fluctuating four-dimensional Z2-Regge lattice and compare with the results of the four-dimensional Ising model on a regular lattice. Particular emphasis is placed on the phase transition of the spin system and the associated critical exponents. We present results from finite-size scaling analyses of extensive Monte Carlo simulations which are consistent with mean-field predictions.